2004
DOI: 10.1377/hlthaff.23.4.184
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Barriers To Adopting And Implementing Computerized Physician Order Entry Systems In U.S. Hospitals

Abstract: Few U.S. hospitals have implemented computerized physician order entry (CPOE) in spite of its effectiveness at preventing serious medication errors. We interviewed senior management at twenty-six hospitals to identify ways to overcome barriers to adopting and implementing CPOE. Within the hospital, strong leadership and high-quality technology were critical. Hospitals that placed a high priority on patient safety could more easily justify the cost of CPOE. Outside the hospital, financial incentives and public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
245
0
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 349 publications
(261 citation statements)
references
References 5 publications
9
245
0
7
Order By: Relevance
“…Research has found that physician resistance is a challenge in the implementation of a new EHR system when switching from a paper-based practice. 7,8,11,15 One might expect that resistance would decrease after a practitioner began using an EHR thereby facilitating the transition to a new system. However, our study findings indicate otherwise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has found that physician resistance is a challenge in the implementation of a new EHR system when switching from a paper-based practice. 7,8,11,15 One might expect that resistance would decrease after a practitioner began using an EHR thereby facilitating the transition to a new system. However, our study findings indicate otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…5 Reasons for the lack of adoption are not fully understood but include physician resistance, financial costs, concerns about privacy, lack of uniform standards, and little information about best practices for implementation. 6,7 Current literature has focused primarily on implementing EHR systems in paper-based practices. [8][9][10][11][12] Practices replacing their EHR legacy system may face unique challenges such as data migration between different vendor products and practitioner's brand loyalty to older EHRs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,[14][15][16][17] Regardless of the study focus, one theme consistently emerges: embedding CPOE in healthcare fundamentally changes the way clinicians coordinate their work activities and collaborate to deliver care. [18][19][20][21] Indeed, in our prior work we identified nine broad categories of unintended adverse consequences related to CPOE, negative impact on workflow emerged as the most frequently occurring theme.…”
Section: Introductionmentioning
confidence: 99%
“…1 CPOE has been shown to decrease medication ordering errors and redundant test ordering, promote practice standardization, and reduce overall healthcare costs. [2][3][4] Despite these benefits, CPOE systems have yet to be widely adopted for several reasons, including the high cost of implementation, clinician resistance to technology, worry regarding practice disruption and loss of productivity, fear of technology failure, and the inability of some CPOE implementations to integrate with existing healthcare systems.…”
Section: Introductionmentioning
confidence: 99%